Prophylactic central neck dissection for papillary thyroid carcinoma:the terms of the debate - Gradoni, P.; Giordano, D.; Oretti, et al., G. (Acta Biomedica Atenei Parmensis, 2010)
An increasing interest in the management of central neck lymph nodes in the surgical treatment of papillary thyroid cancer is observed. While is widely accepted that patients with clinically apparent lymph nodes metastases should undergo compartment-oriented neck dissection, controversy exists about the need for prophylactic central neck dissection. The main issues that have been raised are the following ones: the definition of the anatomic boundaries and terminology of central neck dissection, the value of the recommendations expressed by the most authoritative association, the arguments in favour and against the appropriateness of prophylactic neck dissection, the laterality of central neck dissection. This article aims at reviewing the literature on prophylactic central neck dissection for papillary thyroid cancer in order to clarify some issues and to offer the reader a clear and concise overview of this complex debate.